Perencanaan Sistem Jaringan Perpipaan Distribusi Air Bersih pada Perusahaan Daerah Air Minum (PDAM) - Akhlada Ummaira; Ichsan Syahputra; Muhammad Ridha (Jurnal Teknik Sipil Unaya, 2021)
Water is a natural resource that is very useful in human life. One of the problems that occurred in Kabupaten Aceh Tenggarat, precisely in the city of Kutacane and especially in Kecamtan Babussalam, is the reduced water discharge from the Lawe Sikap river which has been the source of water for the Lawe Sikap PDAM Water Treatment Installation. The aim of this research is to find out the existing clean water distribution piping network system, then an effective alternative piping network system will be planned. The method used in this research is secondary ftom the existing network system. The research of network analysis is using the Pipe Flow Expert program. Evaluation of the existing network using PVC pipe sizes used 4'', 8'' and 12'' diameter, the existing flow velocity is 4.989–7,893 m/sec, exceeds the allowable limit of 3.0–4.5 m/sec and the pressure is still minus. So, the results obtained from the research plan using PVC pipe sizes used are 4 ", 6", 8 "and 12" in diameter. From this research also obtained the results that the flow velocity is 4.004 m/sec and is still within the permitted limit and the pressure is still minus. Based on the results above, it can be concluded that the existing network must be re-planned. The suggestion that the author can give to produce a sufficient pressure is to use a pump system